Enhanced Synthetic Access to Tris-CF(3)-Substituted Corroles - Yadav, Pinky (Org Lett, 2020)
Separate focus on the oligomerization and oxidative cyclization steps required for the synthesis of 5,10,15-tris(trifluoromethyl)corrole revealed [bis(trifluoroacetoxy)iodo] benzene (PIFA) as a superior alternative oxidant. Under optimized conditions, the pure free-base corrole was obtained with a sixfold increase in chemical yield and an eleven-fold rise in isolated material per synthesis. The corresponding gallium(III) and manganese(III) complexes were isolated by adding the appropriate metal salt prior to corrole purification.